Fostering student digital wellbeing through digital storytelling integrated with peer assessment - Prabowo, Thoriq Tri; Sitthiworachart, Jirarat; Sriwisathiyakun, Kanyarat (My University, 2025)
Learning activities, which blend digital storytelling with peer assessment, foster the development of crucial digital skills. They require students to engage in writing, information gathering, utilizing technology tools, synthesizing information, and providing constructive feedback on their peers' work. This study developed and used digital storytelling integrated with peer assessment (DSIPA) to promote digital wellbeing. This study has several objectives: 1) to determine whether this integrated digital storytelling significantly improved student digital wellbeing skills compared to students who receive digital storytelling with teacher feedback (DSITF); 2) to investigate the types of peer feedback the students provided in the peer assessment activities; and 3) to explore the students' perspectives on the learning activity with this integrated digital storytelling to promote digital wellbeing. DSIPA was implemented and evaluated; 72 Library and Information Science (LIS) students from UIN Sunan Kalijaga Yogyakarta, Indonesia, were selected using simple random sampling. DSIPA was compared to DSITF, with each group consisting of 36 students. The developed DSIPA lesson plan was used for guiding the six-week learning activities. A digital wellbeing scale with 5-point Likert scale was used. MANOVA analysis, with a 0.05 level, revealed significant difference for digital wellbeing between DSIPA and DSITF. Students who learnt with DSIPA obtained higher scores than students who learnt with DSITF. The results of peer feedback analysis reflected a generally positive peer feedback culture, characterized by a balance of praise and constructive criticism. A thematic analysis of students' open-ended survey responses revealed their positive perspective on the learning activity. They felt it significantly improved their digital wellbeing, along with boosting their motivation, engagement, and academic achievement. To enhance the effectiveness, developing DSIPA activities with clear objectives and structured outcomes, supported by adequate training and resources, is recommended. Actively monitoring collaborative work and implementing engaging ice-breaking activities will also promote productive learning environments.
Keywords: Digital storytelling; Digital wellbeing; Indonesia; LIS students; Peer assessment